2013
DOI: 10.1080/1359432x.2013.800678
|View full text |Cite
|
Sign up to set email alerts
|

Do core self-evaluations and coping style influence the perception of job insecurity?

Abstract: Over the last few decades, increased flexibility and lack of stability in employment has made job insecurity a work stressor that affects more and more employees. Since worrying about potential job loss (quantitative job insecurity) or possible loss of valued job features (qualitative job insecurity) constitutes a subjective perception, it has been claimed that personality factors may be decisive for job insecurity perceptions. Furthermore, the perception of a stressor, in this case job insecurity, could be ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Although we did not investigate environmental variables in our sample, biographical variables (none of which reached statistical significance), work locus of control and sense of coherence explained 20% of the variance in both cognitive and affective job insecurity. In their investigation of the effects of core self-evaluations and coping on perceptions of quantitative and qualitative job insecurity, Låstad et al (2014) found that these variables predicted 7% of the variance in quantitative, and 11% of the variance in qualitative job insecurity in a longitudinal analysis. In a much larger sample from financial institutions in South Africa, Bosman et al (2005) found the addition of work locus of control (additional to demographics) to predict 14% of the variance in job insecurity 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we did not investigate environmental variables in our sample, biographical variables (none of which reached statistical significance), work locus of control and sense of coherence explained 20% of the variance in both cognitive and affective job insecurity. In their investigation of the effects of core self-evaluations and coping on perceptions of quantitative and qualitative job insecurity, Låstad et al (2014) found that these variables predicted 7% of the variance in quantitative, and 11% of the variance in qualitative job insecurity in a longitudinal analysis. In a much larger sample from financial institutions in South Africa, Bosman et al (2005) found the addition of work locus of control (additional to demographics) to predict 14% of the variance in job insecurity 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding biographical antecedents, Kinnunen and Nätti (1994) found perceived unemployment risk to correlate with gender, age, and level of education. Låstad, Berntson, Näswall and Sverke (2014) showed age to correlate with qualitative job insecurity, while Kinnunen et al (1999) also suggest that men experience higher job insecurity than women. In terms of the outcomes of job insecurity, age has been shown to be significant, in that older employees are worse affected (Cheng & Chan, 2008).…”
Section: Overview: General and Personality Antecedents Of Job Insecuritymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in this article we deal with three groups of job security predictors: background characteristics, job characteristics, and organizational characteristics, as defined by Ištoňová and Fedáková (2015) and based on a literature review primarily on the topic of job insecurity. The background characteristics that appear to be the most relevant predictors of job (in)security are age, gender, and education, according to papers by Näswall and De Witte (2003), Munoz de Bustilloand and de Pedreza (2010), Ito and Brotheridge (2007), Låstad et al (2014), and Kirves et al (2011). Previous experience of unemployment is a significant predictor of perceived job security in the future workplace (De Witte, 1999).…”
Section: Job Security and Its Predictorsmentioning
confidence: 99%